2002
DOI: 10.1002/etc.5620210807
|View full text |Cite
|
Sign up to set email alerts
|

Using Monte Carlo techniques to judge model prediction accuracy: Validation of the pesticide root zone model 3.12

Abstract: Individuals from the Federal Insecticide, Fungicide, and Rodenticide Act (FIFRA) Environmental Model Validation Task Force (FEMVTF) Statistics Committee periodically met to discuss the mechanism for conducting an uncertainty analysis of Version 3.12 of the pesticide root zone model (PRZM 3.12) and to identify those model input parameters that most contribute to model prediction error. This activity was part of a larger project evaluating PRZM 3.12. The goal of the uncertainty analysis was to compare site-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…[38][39][40] e choice of the shapes and types of distributions re ects the magnitude, range, and interpretation of each parameter. erefore, as recommended in previous reports, 10,30) the types of PDFs for the selected parameters remained unchanged among scenarios, while the means and the variances of PDFs were scenario (herbicides)-dependent ( Table 2). In general, the means, variances and ranges of an input have more in uence on the output uncertainty than the form of the distribution.…”
Section: Monte Carlo Simulation and Parameter Selectionmentioning
confidence: 52%
See 3 more Smart Citations
“…[38][39][40] e choice of the shapes and types of distributions re ects the magnitude, range, and interpretation of each parameter. erefore, as recommended in previous reports, 10,30) the types of PDFs for the selected parameters remained unchanged among scenarios, while the means and the variances of PDFs were scenario (herbicides)-dependent ( Table 2). In general, the means, variances and ranges of an input have more in uence on the output uncertainty than the form of the distribution.…”
Section: Monte Carlo Simulation and Parameter Selectionmentioning
confidence: 52%
“…For modeling the pesticide fate in environment, incorporating a probabilistic approach such as the Monte Carlo (MC) technique 10,19,32) is useful for the evaluation of modeling uncertainties associated with input parameters as well as uncertainties due to the model itself. Since the MC technique provides insight into the model behavior, it was helpful to estimate the uncertain model input and increase the reliability of the model.…”
Section: Monte Carlo Simulation and Parameter Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…It does not simulate the transport of pesticide through the broader environment (e.g., streams, basin outlets). PRZM has been used extensively and several studies have shown that the model produces reasonable estimates (e.g., Acc e p ted P r e p r i nt Carbone et al 2002;Singh and Jones 2002;Warren-Hicks et al 2002;Farenhorst et al 2009) while requiring relatively low computational time (McQueen et al 2007). …”
Section: 4 P E S T I C I D E T R a N S P O R T M O D E Lmentioning
confidence: 99%